PENGARUH SELF ASSESSMENT SYSTEM, PEMERIKSAAN PAJAK, DAN PENAGIHAN PAJAK TERHADAP PENERIMAAN PAJAK PERTAMBAHAN NILAI (PPN) PADA KPP PRATAMA SERANG BARAT - Efi Tajuroh Afiah; Nugrahini Kusumawati; Maria Ulfa (LPPM Universitas Bina Bangsa, 2024)
The purpose of this study is to determine the effect of the Self Assessment System, Tax Inspection, and Tax Collection on Value Added Tax (VAT) revenues at KPP Pratama Serang Barat for the 2017-2021 period. The method used is descriptive quantitative with a quantitative research approach. WP Badan research population registered pkp per month at KPP Pratama Serang Barat office during the period 2017-2021. The total number of the entire sample is 60. The results in this study indicate that partially Self Assessment System affects the recipient of VAT. Tax Inspection and Tax Collection have no effect on VAT receipts. Simultaneously, the Self Assessment System, Tax Inspection, and Tax Collection affect VAT receipts